A multiprofessional client-centred guide to implementing assistive technology for clients with cognitive impairments. - Bartfai, A.; Boman, I.-L. (Technology & Disability, 2008)
OBJECTIVE: The aim was to develop a framework for prescribing assistive technology (AT) for people with cognitive impairment and provide guidelines for clinical practice. METHODS: A qualitative approach was used to develop and validate the guide. RESULTS: The guide is directed mainly towards occupational therapists and neuropsychologists. It comprises six main steps, 1. Meeting the client, 2. Goal setting, 3. Assessment, 4. Choice of relevant devices, 5. Teaching and training plan, 6. Evaluation and follow-up. Special emphasis is put on the empowerment of the client and their significant others in the process. The guide applies to a wide range of clinical diagnoses involving cognitive impairment.CONCLUSIONS: The guide involves a number of steps requiring substantial clinical resources, which is a challenge but at the same time it might promote an understanding for the complexity of the process among clients, their significant others, rehabilitation professionals and resource providers. The expectations are that more structured and individually adjusted procedures result in a more successful long term use of AT.